An assessment of the processing and physicochemical factors contributing to the microbial contamination of salpicão, a naturally-fermented Portuguese sausage - Cadavez, Vasco (2017)
Complete microbiological, physicochemical and environmental longitudinal data were obtained from factory surveys in order to elucidate risk factors leading to the survival of Enterobacteriaceae, Staphylococcus aureus and Listeria monocytogenes in salpicão sausage. A total of six batches were surveyed from two factories; one added nitrite and polyphosphates in their formulation (Factory II). The addition of polyphosphates slowed down fermentation, which favoured the increase in Enterobacteriaceae (∼0.5 log CFU/g), S. aureus (∼0.5 log CFU/g) and L. monocytogenes (∼70 CFU/g) until maceration. Maceration should be regarded as a critical stage in the control of S. aureus in salpicão, as longer maceration (p = 0.033), higher temperatures of maceration (p = 0.018) and pH of macerated meat (p = 0.079) led to higher S. aureus counts in the final product. The main hurdle controlling S. aureus in salpicão is the pH. For L. monocytogenes and Enterobacteriaceae, at least three hurdles hinder their viability: low Aw (p = 0.010; 0.012), smoking (p < 0.0001; 0.020) and nitrite (p = 0.158; 0.105). Cross-contamination, especially during mixing, should be avoided as it is an important factor explaining the increase in Enterobacteriaceae (p = 0.041), S. aureus (p = 0.015) and L. monocytogenes (p = 0.082) on a batch basis. There is a need to optimise the acidification process and reinforce good hygiene practices